Zinc oxide nanoparticles based microfluidic immunosensor applied in congenital hypothyroidism screening - Seia, Marco Abel (2014)
In this article, we present an innovative approach for congenital hypothyroidism (CHT) screening. This pathology is the most common preventable cause of mental retardation, affecting newborns around the world. Its consequences could be avoided with an early diagnosis through the thyrotropin (TSH) level measurement. To accomplish the determination of TSH, synthesized zinc oxide (ZnO) nanobeads (NBs) covered by chitosan (CH), ZnO-CH NBs, were covalently attached to the central channel of the designed microfluidic device. These beads were employed as platform for anti-TSH monoclonal antibody immobilization to specifically recognize and capture TSH in neonatal samples without any special pretreatment. Afterwards, the amount of this trapped hormone was quantified by horseradish peroxidase (HRP)-conjugated anti-TSH antibody. HRP reacted with its enzymatic substrate in a redox process, which resulted in the appearance of a current whose magnitude was directly proportional to the level of TSH in the neonatal sample. The structure and morphology of synthesized ZnO-CH NBs were characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD). The calculated detection limits for electrochemical detection and the enzyme-linked immunosorbent assay procedure were 0.00087 μUI mL-1 and 0.015 μUI mL-1, respectively, and the within- and between-assay coefficients of variation were below 6.31 % for the proposed method. According to the cut-off value for TSH neonatal screening, a reasonably good limit of detection was achieved. These above-mentioned features make the system advantageous for routine clinical analysis adaptation.